GEOLOGICAL MAPPING OF TEGINA AND ENVIRONS NORTH-CENTRAL NIGERIA - BARKA J.; TABALE, R.P. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Tegina and environs is situated within the north-central part of Nigeria. Geological mapping of Tegina and environs was carried out to produce a geological and structural map of the area with a view of updating the existing information on the geology of Nigeria. Lithologies mapped include migmatite-gneiss, schist and medium to coarse-grained granite. The dominant lithology in the area is schist covering more than 50% of the total area. Structures observed in the area are joints, veins, dykes, foliations, faults and folds and are mostly observed on the migmatite-gneiss and granitic rocks only. The NE-SW structures dominate, with minor trends of structures in the NW-SE and E-W directions. The flows of streams in the study area were structurally controlled. From field evidences, the geological and structural map of the area was produced.